Digital innovation and performance of manufacturing firms: An affordance perspective. (January 2023) - Liu, Yang; Dong, Jiuyu; Mei, Liang; Shen, Rui
Abstract: We explore the underlying mechanisms and institutional conditions of profiting from digital innovation in the context of manufacturing firms. Building on affordance theory, we propose that digital innovations positively affect manufacturing firms' performance via innovation speed and operational efficiency due to the affordance of digital technology. Moreover, the interactions between digital and institutional affordances suggest that the intellectual property rights (IPR) protection system (i.e. IPR regime and its enforcement) negatively moderates the relationship between digital innovation adoption and innovation speed, as well as operational efficiency. Results from a longitudinal sample of Chinese listed firms support our hypotheses. Our findings contribute to the emerging literature on profiting from digital innovation and provide managerial implications for manufacturing firms in emerging markets. Graphical abstract: Image 1 Highlights: Affordance theory provides a clear picture for understanding how firms profit from digital innovations. Innovation speed and operational efficiency mediate the digital innovation– performance relationship. An overall picture of the roles the IPR protection system plays in how firms profit from digital innovations is presented.